A review on studies of phrasal verb constructions in ESL context - Jahedi, Maryam; Mukundan, Jayakaran (Australian International Academic Centre, 2015)
This paper aims to give an overview of studies on phrasal verbs in three decades to present the theoretical and methodological issues, as well as the findings of research. Moreover, this review reveals the developments and paradigm shifts occurred in this area. Previous studies have shown that the research findings have not been incorporated into classroom activities and English Language Teaching (ELT) materials. The paper claims that the number of research on the use of phrasal verbs in ESL textbooks is limited and, therefore, further research is needed to examine how phrasal verbs are treated in textbooks in order to help ELT materials developers to present these items more effectively based on research findings.